2020
DOI: 10.1186/s13195-020-00733-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of RALYL in Alzheimer’s disease reserve by network-based approaches

Abstract: Background Alzheimer’s disease (AD) reserve theory is based on specific individual characteristics that are associated with a higher resilience against neurodegeneration and its symptoms. A given degree of AD pathology may contribute to varying cognitive decline levels in different individuals. Although this phenomenon is attributed to reserve, the biological mechanisms that underpin it remain elusive, which restricts translational medicine research and treatment strategy development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…Among the top ten upregulated genes were genes known for their roles in neurodevelopment including Heparan Sulfate 6-O-Sulfotransferase 3 ( Hs6st3 ), Adhesion G Protein-Coupled Receptor L3 ( Adgrl3 ), Contactin 5 ( Cntn5 ), and Neuregulin 1 ( Nrg1 ) ( Mei and Xiong, 2008 ; Cocchi et al, 2016 ; El Hajj et al, 2017 ; Moon and Zhao, 2021 ). In addition, SCA1 PCs had increased expression of RALY RNA Binding Protein-like (Ralyl) ,which is known as an Alzheimer’s disease cognitive reserve gene ( Zhang et al, 2020 ) ( Figures 2A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the top ten upregulated genes were genes known for their roles in neurodevelopment including Heparan Sulfate 6-O-Sulfotransferase 3 ( Hs6st3 ), Adhesion G Protein-Coupled Receptor L3 ( Adgrl3 ), Contactin 5 ( Cntn5 ), and Neuregulin 1 ( Nrg1 ) ( Mei and Xiong, 2008 ; Cocchi et al, 2016 ; El Hajj et al, 2017 ; Moon and Zhao, 2021 ). In addition, SCA1 PCs had increased expression of RALY RNA Binding Protein-like (Ralyl) ,which is known as an Alzheimer’s disease cognitive reserve gene ( Zhang et al, 2020 ) ( Figures 2A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Among top ten upregulated genes were Heparan Sulfate 6-O-Sulfotransferase 3 ( Hs6st3 ), Adhesion G Protein-Coupled Receptor L3 ( Adgrl3 ), Contactin 5 ( Cntn5 ), and Neuregulin 1 ( Nrg1 ) known for their roles in neurodevelopment [47][48][49][50]. In addition, SCA1 PCs had increased expression of RALY RNA Binding Protein-like (Ralyl) known as Alzheimer’s disease cognitive reserve gene [51] ( Figures 2A-C ). Among upregulated genes were also three vacuolar V-type ATP-ase subunits ( Atp6v0c , Atpgv0a1 , and Atp6v1h ) and Slc32a1 , encoding vesicular GABA and Glycine Transporter (VGAT) indicating that synaptic vesicles SCA1 PCs may have increased GABA content.…”
Section: Resultsmentioning
confidence: 99%
“…For PCs we validated the findings from previous studies but also identified novel, potentially compensatory gene expression changes such as increased expression of Ralyl , Atp6v0c , Atpgv0a1 , Atp6v1h , Atp6v and Slc32a1. Ralyl is an RNA binding protein known for its neuroprotective role in Alzheimer’s [51]. Increased expression of three vacuolar V-type ATP-ase subunits ( Atp6v0c , Atpgv0a1 , and Atp6v1h ) that provide electrochemical gradient to fill synaptic vesicles with GABA and Slc32a1 , encoding vesicular GABA and Glycine Transporter (VGAT) that transports GABA in the vesicles may suggest increased GABA content in PCs synaptic vesicle.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Ralyl expression decreases with Alzheimer's progression. Subjects with Alzheimer's disease reserves show significantly higher Ralyl expression compared with those without Alzheimer's disease reserves (Zhang et al, 2020). Ralyl is related to cancer cell metastasis and poor prognosis in patients with liver cancer.…”
Section: Granule Cell Genementioning
confidence: 93%
“…The Raly-like recognition motif (Ralyl) is identified as an important characteristic gene by the mRMR, and its encoded RNA binding protein affects embryonic development (Ji et al, 2003a). A previous study pointed out that Ralyl may be related to Alzheimer's disease (Zhang et al, 2020). Researchers revealed that Ralyl is a hub gene in the brain transcriptome module of patients with Alzheimer's disease and is highly associated with Alzheimer's reserve-related phenotypes.…”
Section: Granule Cell Genementioning
confidence: 99%